Contextual Analysis of Bilingual Program at SD Muhammadiyah Jakarta: An Evaluative Case Study Based on the CIPP Model and Ecological Systems Theory - Zulfida, Sri; Suseno, Muchlas; Setiadi, Samsi (LPPM Universitas PGRI Semarang, 2025)
This study aims to evaluate the implementation of the bilingual programme at SD Muhammadiyah Jakarta using the CIPP (Context, Input, Process, Product) evaluation model combined with Bronfenbrenner's ecological systems theory. This topic is important as it reflects the integrative efforts of Islamic-based education with the global need for multilingual competencies, particularly in the context of urban Islamic schools facing social, cultural, and policy complexities. This study employs a qualitative approach with an intrinsic case study design. Data were collected through classroom observations, in-depth interviews with students, teachers, school principals, and parents, as well as school documentation. Analysis was conducted thematically based on the CIPP dimensions and ecological systems. The findings indicate that the bilingual programme is implemented systematically with strong cross-system support, including active participation from teachers, principals, and parents. Translanguaging strategies have proven effective in helping students understand the material without neglecting Islamic values. These findings expand the application of the CIPP model and ecological theory in the context of values-based bilingual education. This research contributes to the development of a holistic evaluative approach and provides a policy basis for Islamic schools to implement contextual and sustainable bilingual programmes. Further research is recommended to adopt a longitudinal and mixed-methods design to strengthen the validity and scope of the findings.